Identifying Lung Cancer Patients Suitable for Segmentectomy: A Brief Review - Wang, Chunguo; Wu, Sikai; Zhang, Rongwei; Jin, Ke; Qian, Yicheng; Mao, Ning; Liu, Yun; Zhang, Miao; Zhang, Ke; Wang, Renfeng; Huang, Gang; Zhang, Min; et al. (Frontiers in Surgery, 2021)
Background: In 1995, a clinical randomized controlled study (RCT) conducted by the Lung Cancer Study Group (LCSG) pointed out that the lobectomy was the gold standard for treating early lung cancer. However, with the development of technology, the results of several retrospective studies have shown that the efficacy of pulmonary segmentectomy is equivalent to that of lobectomy. Currently, it is still controversial whether segmental resection or lobectomy should be performed for early lung cancer. Thus, we aim to summarize the indications of segmentectomy. Methods: To conduct the review, previous researches involving indications of segmentectomy were collected from the literature using Pubmed. These articles were published and accepted in English in the medical literature from 2013 to 2020. We have focused on segmentectomy and its indications. Results: A total of 176 articles were retrieved from the Pubmed database, of which 31 articles included indications for segmentectomy. We summarized the relevant content, and the potential and prospect of segmentectomy for the treatment of lung cancer were emphasized. Conclusions: These findings have a number of important implications for future practice. Pulmonary segmentectomy is a very vital surgical procedure for select patients with lung cancer, which provides a novel approach for the treatment of lung cancer and the survival of lung cancer patients.